Intention to Quit Tobacco Use and its Determinants Among Adolescent Tobacco Users Residing in Slum Areas of Bhubaneswar, India: A Cross-Sectional Study - Panigrahi, Ansuman; Sharma, Dheeraj; Maharana, Sabita (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Intention to quit is the initial step and a strong predictor of quitting tobacco use.Objective The aim of this study was to estimate the prevalence and determinants of intention to quit tobacco use among adolescent tobacco users residing in the slum areas of Bhubaneswar, India.Materials and Methods A community-based cross-sectional study was performed during the year 2017–2018 involving 152 adolescent tobacco users residing in the slums of Bhubaneswar. Multistage cluster random sampling was used to select the study areas.Results Ninety-three (61.2%) adolescents had the intention to quit tobacco use. Multivariate logistic regression analysis revealed that the odds of intention to quit tobacco use was significantly higher in adolescents who used it for less than 5 years' duration (adjusted odds ratio (aOR): 2.59; 95% confidence interval [CI]: 1.14–5.87), those used first tobacco of the day between 31 and 60 minutes after waking up in the morning (aOR: 2.60; 95% CI: 1.17–5.79) or more than 60 minutes after waking up (aOR: 6.69; 95% CI: 2.28–19.61), and those who noticed anti-tobacco messages in any media in the past 30 days (aOR: 2.70; 95% CI: 1.02–7.14).Conclusion The prevalence of intention to quit tobacco use among slum adolescents of Bhubaneswar is 61.2%, which can be enhanced by incorporating the determinants of the intention to quit tobacco use in the existing anti-tobacco schemes.
Keywords: intention to quit; adolescent; tobacco use; anti-tobacco messages; slum